(untitled) (Journal of Humanitarian and Applied Sciences, 2020)
The character of Sultan Abdulhamid II is one of the most historical Islamic figures who received a lot of distortion and injustice, as it appeared in a period when events, facts and ambitions were intertwined in a country that was going through a very dangerous situation, as the aspirations of European countries aspired to colonization and expansion conquered it, so it was the goal and purpose and accompanied by that attack was a tremendous amount of lies, distortion and exaggeration in events and facts without proof or credibility. Thus, this character who assumed power at that stage was depicted with the most horrific descriptions, so it was considered a violent, bloody, authoritarian, unjust, but was it realistic? A tracker of all these exaggerations knows that the matter had an aim and a goal, and since the beginning of its rule, this character showed awareness and knowledge of what is being hatched for this state. This early feeling of what is happening dominated the colonial eyes that sought with all possible capabilities to mix papers and historical events by using the minorities and Jews in order to raise the international opinion against it, as it knows that the survival of this Sultan is a stumbling block ahead of all its ambitions, as it was clear in all of these situations, and the extent and size of this campaign directed to this character was revealed, including the distortion it was carried out when those matters appeared in the way he dealt with federalists and minorities, and what was published in the (Protocols of the Elders of Zion, and Herzl’s memoirs) to clarify the nature of that character and the difficulty of dealing with it, it stood before the fulfillment of their ambitions, despite the extremely difficult circumstances in which the Ottoman Empire lived, not to mention his early awareness of the conspiracies of Zionism and global Freemasonry that ended in his isolation and his distance from The reins of government. This character is worth a lot of in-depth studies in order to shed light more accurately, credibly and fairly historical review of all events and facts that she lived or contributed to, without distortion, exaggeration and exaggerated exploitation.